Reactive wetting of amorphous silica by Sn0.3Ag0.7Cu-xTi (x = 1 and 3 wt.%) alloys at 800–900 °C. Issue 10 (July 2019) - Sui, Ran; Wang, Jianbin; Ci, Wenjuan; Lin, Qiaoli; Yang, Hongyu
Abstract: The wetting of SiO2 by molten Sn0.3 Ag0.7 Cu(SAC)- x Ti ( x = 1 and 3 wt.%) was studied by using the modified sessile drop method at 800–900 °C under a high vacuum. The small addition of Ti into SAC alloy can improve wettability, significantly. Because the SnTi intermetallics with high melting point covered Ti addition and blocked further dissolution of Ti, and thus Ti cannot be dissolved completely when the nominal concentration of Ti was 3 wt.%. The reaction products at liquid/solid interface are Ti5 Si3 and TiO. The spreading dynamics can be described by reaction product control model. The spreading may be coupled firstly with the precipitation of Ti5 Si3 and TiO together meanwhile be affected by the dissolution of Ti addition, and then the precipitation of TiO alone. The final wettability was determined both by the wetting character of reaction products and also TiO adsorption at interface.